Substance Misuse in Psychosis 2002
DOI: 10.1002/9780470713846.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Start Over and Survive: A Brief Intervention for Substance Misuse in Early Psychosis

Abstract: At around 15 years of age Jake began using drugs occasionally with his friends. During his late teenage years, he wanted to become a DJ and spent a lot of time at clubs, where he used amphetamine and ecstasy. His use of alcohol and cannabis also increased at this time, as he found these substances would "calm his nerves" and help him "chill out". When Jake was 21, his parents started to put pressure on him to get a "proper job", and he moved out of their home to live with his girlfriend, who occasionally used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…The GAF is widely used in studies of treatment effectiveness and the relative simplicity, reliability and validity of scale has seen it used in a wide variety of clinical and research settings Substance misuse: The Kavanagh drug check (revised version) was used to assess the consumption of cannabis, alcohol and class A drugs within the last month Deliberate self‐harm and aggression: Violent incidents were assessed by self‐report and information from collateral informants including health professionals, using a shortened version of the MacArthur study questionnaire, modified for UK use …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GAF is widely used in studies of treatment effectiveness and the relative simplicity, reliability and validity of scale has seen it used in a wide variety of clinical and research settings Substance misuse: The Kavanagh drug check (revised version) was used to assess the consumption of cannabis, alcohol and class A drugs within the last month Deliberate self‐harm and aggression: Violent incidents were assessed by self‐report and information from collateral informants including health professionals, using a shortened version of the MacArthur study questionnaire, modified for UK use …”
Section: Methodsmentioning
confidence: 99%
“…(revised version) was used to assess the consumption of cannabis, alcohol and class A drugs within the last month. 34…”
Section: Substance Misuse: the Kavanagh Drug Checkmentioning
confidence: 99%
“…Biographical details and the history of the disorder and its treatment were obtained from the patient, relatives and hospital file. Screening for misuse used the Alcohol Use Disorders Identification Test (AUDIT) [12], the Severity of Dependence Scale (SDS) [13] and the DrugCheck [14]. The DrugCheck comprised quantity/frequency indices over the previous 3 months, plus a 13-item problem list (PL) that assessed the functional impact of the most problematic substance.…”
Section: Methodsmentioning
confidence: 99%
“…The DrugCheck comprised quantity/frequency indices over the previous 3 months, plus a 13-item problem list (PL) that assessed the functional impact of the most problematic substance. All three measures have high sensitivity and specificity in detecting substance misuse in psychosis [14,15]. Diagnoses of substance use disorders were confirmed using the Composite International Diagnostic Interview-Auto v2.1 (CIDI-Auto) [16], sections B (tobacco), J (alcohol) and L (substance-related disorders), which has acceptable reliability and validity in substance misuse [17].…”
Section: Methodsmentioning
confidence: 99%
“…(2000) have shown that psycho‐education group therapy and integrated group therapy, respectively, are effective with people who have bipolar disorders and substance misuse problems. Researchers in Australia evaluated a brief intervention for dual diagnosis and showed that motivational interviewing was associated with reduction in substance misuse compared with standard care (Kavanagh et al . 2003).…”
Section: Introductionmentioning
confidence: 99%